An analysis of the Department of Social Welfare & Pensions' capacity to respond to needs & social problems of the people in Venda - Davhana, Tendani Doreen (Department of Social Development, 2024)
This study analyses the Department of Welfare & Pension's capacity to respond to the needs and social problems of the people in Venda. The analysis focused on the internal and external factors that have a bearing or impact on the Department's service provision. The internal organizational factors covered aspects such as the structure of welfare service provision, some management processes, resource limitations, human resource management, and methods or approaches used to address the needs and social problems, other employment conditions and the welfare approach at state level. The external factors covered the unfavourable political and socio-economic conditions experienced by the Welfare Department and it's clientele. The study also describes and examines the types of social problems and needs of the people, and what the Department is actually able to provide. How the Department responds to problems and needs is examined in relation to the social work profession. An exploratory descriptive approach was used. Data was gathered from primary and secondary sources. Observations and interviewing were used for collecting primary data. Both structured and unstructured interviews were carried out with people belonging to various professions, Government Departments and welfare organizations. The needs and social problems of the clients were quantified in terms of the Department's statistical records and waiting lists. The services rendered by the Department of Social Welfare and Pensions were quantified in terms of clients being served, the number of projects and programmes undertaken, and available welfare institutions. The findings revealed that there are problems surrounding . the analyzed factors. The Department's capacity to respond to needs is limited, and is also negatively affected by many factors. (iv) The analysis demonstrated that the most serious constraints of the Department are the discrepancy between needs/problems and· resources, as well as the over utilization of a single social work method of problem solving. Serious problems exist as regards human resource management, motivation, job satisfaction, and other employment conditions. Such problems have a negative impact on the provision of social . welfare services. The welfare approach at State level, Welfare policy, and Venda's economic dependency on South Africa, also have serious implications for the Department's response to needs and problems. The study's recommendati6ns draw attention to the need for improvement in the areas or factors examined. An alternative organizational design to improve the Welfare Department's capacity, is suggested, and details on how it could work are provided.